Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the quotient [tex]\( Q \)[/tex] and the remainder [tex]\( R \)[/tex] when dividing the polynomial [tex]\( 24x^3 - 14x^2 + 20x + 6 \)[/tex] by the polynomial [tex]\( 4x^2 - 3x + 5 \)[/tex], we will perform polynomial division.
We are given the polynomials:
[tex]\[ P(x) = 24x^3 - 14x^2 + 20x + 6 \][/tex]
[tex]\[ D(x) = 4x^2 - 3x + 5 \][/tex]
1. First Division Step:
[tex]\[ \frac{24x^3}{4x^2} = 6x \][/tex]
So, the first term in the quotient is [tex]\( 6x \)[/tex].
2. Multiply and Subtract:
[tex]\[ 24x^3 - 14x^2 + 20x + 6 - (6x \cdot (4x^2 - 3x + 5)) = 24x^3 - 14x^2 + 20x + 6 - (24x^3 - 18x^2 + 30x) \][/tex]
[tex]\[ = 24x^3 - 14x^2 + 20x + 6 - 24x^3 + 18x^2 - 30x \][/tex]
[tex]\[ = ( -14x^2 + 18x^2 ) + ( 20x - 30x ) + 6 \][/tex]
[tex]\[ = 4x^2 - 10x + 6 \][/tex]
3. Second Division Step:
[tex]\[ \frac{4x^2}{4x^2} = 1 \][/tex]
So, the next term is [tex]\( 1 \)[/tex].
4. Multiply and Subtract:
[tex]\[ 4x^2 - 10x + 6 - (1 \cdot (4x^2 - 3x + 5)) = 4x^2 - 10x + 6 - (4x^2 - 3x + 5) \][/tex]
[tex]\[ = 4x^2 - 10x + 6 - 4x^2 + 3x - 5 \][/tex]
[tex]\[ = ( -10x + 3x ) + ( 6 - 5 ) \][/tex]
[tex]\[ = -7x + 1 \][/tex]
So, the quotient [tex]\( Q \)[/tex] is:
[tex]\[ Q = 6x + 1 \][/tex]
And the remainder [tex]\( R \)[/tex] is:
[tex]\[ R = -7x + 1 \][/tex]
Therefore, presenting the result, we have:
[tex]\[ Q = 6x + 1 \][/tex]
[tex]\[ R = -7x + 1 \][/tex]
So, the division [tex]\( (24x^3 - 14x^2 + 20x + 6) \div (4x^2 - 3x + 5) \)[/tex] yields:
[tex]\[ \left(24 x^3 - 14 x^2 + 20 x + 6\right) \div \left(4 x^2 - 3 x + 5\right) = (6x + 1) + \frac{-7x + 1}{4 x^2 - 3 x + 5} \][/tex]
We are given the polynomials:
[tex]\[ P(x) = 24x^3 - 14x^2 + 20x + 6 \][/tex]
[tex]\[ D(x) = 4x^2 - 3x + 5 \][/tex]
1. First Division Step:
[tex]\[ \frac{24x^3}{4x^2} = 6x \][/tex]
So, the first term in the quotient is [tex]\( 6x \)[/tex].
2. Multiply and Subtract:
[tex]\[ 24x^3 - 14x^2 + 20x + 6 - (6x \cdot (4x^2 - 3x + 5)) = 24x^3 - 14x^2 + 20x + 6 - (24x^3 - 18x^2 + 30x) \][/tex]
[tex]\[ = 24x^3 - 14x^2 + 20x + 6 - 24x^3 + 18x^2 - 30x \][/tex]
[tex]\[ = ( -14x^2 + 18x^2 ) + ( 20x - 30x ) + 6 \][/tex]
[tex]\[ = 4x^2 - 10x + 6 \][/tex]
3. Second Division Step:
[tex]\[ \frac{4x^2}{4x^2} = 1 \][/tex]
So, the next term is [tex]\( 1 \)[/tex].
4. Multiply and Subtract:
[tex]\[ 4x^2 - 10x + 6 - (1 \cdot (4x^2 - 3x + 5)) = 4x^2 - 10x + 6 - (4x^2 - 3x + 5) \][/tex]
[tex]\[ = 4x^2 - 10x + 6 - 4x^2 + 3x - 5 \][/tex]
[tex]\[ = ( -10x + 3x ) + ( 6 - 5 ) \][/tex]
[tex]\[ = -7x + 1 \][/tex]
So, the quotient [tex]\( Q \)[/tex] is:
[tex]\[ Q = 6x + 1 \][/tex]
And the remainder [tex]\( R \)[/tex] is:
[tex]\[ R = -7x + 1 \][/tex]
Therefore, presenting the result, we have:
[tex]\[ Q = 6x + 1 \][/tex]
[tex]\[ R = -7x + 1 \][/tex]
So, the division [tex]\( (24x^3 - 14x^2 + 20x + 6) \div (4x^2 - 3x + 5) \)[/tex] yields:
[tex]\[ \left(24 x^3 - 14 x^2 + 20 x + 6\right) \div \left(4 x^2 - 3 x + 5\right) = (6x + 1) + \frac{-7x + 1}{4 x^2 - 3 x + 5} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.